INFLUENCE OF AUSTEMPERING TIME AND AUSTEMPERING TEMPERATURE IN MICROSTRUCTURE AND MECHANICAL PROPERTIES IN AUSTEMPERED DUCTILE IRON - Tissi, Giulliana Victória; da Fonseca, Gláucio Soares (International Journal of Research -GRANTHAALAYAH, 2020)
Austempered Ductile Iron (ADI) has excellent mechanical properties related to its microstructure ausferrite, and with the cycle of austempering heat treatment, many mechanical properties can be obtained from the same alloy, simply changing the time and temperature. To evaluate the influence of austempering time and temperature on the ADI, analyzed the modifications in the microstructures and mechanical properties of the samples of ductile iron, subjected to austempering heat treatment with austenitizing time and temperature of 910 °C and 90 minutes and during the austempering bath, the samples were submitted to different temperatures, 300, 320, 340, 360 e 380 °C, and for four different times for each temperature, 75, 110, 145 and 180 minutes. For the microstructural analysis, the microscopic techniques were used: optical and scanning electron and mechanical properties were obtained by mechanical testing of hardness and impact. The results show that there is a relationship between austempering temperature with microstructure and mechanical properties. The highest retained austenite and energy absorbed were 25.73% and 130 J, respectively, for the austempered sample at 380 °C and 180 minutes and the highest hardness value was 458 HB for the austempered sample at 300 °C and 75 minutes.